The attitudes characterizing humans and giants in two folktales from central Sulawesi - Simon Arsa Manggala (Journal of Applied Studies in Language, 2023)
This paper aims at providing a critical alternative framework for reading folktales from Indonesia from linguistic viewpoints. The choice of linguistic items in tales is significant to investigate since folktales serve as a tool to teach values to children, and they share similar patterns. By utilizing the appraisal analysis, this research attempts to discuss the characterization of humans and giants in the English version of two folktales from Central Sulawesi, a province in Indonesia. The folktales are entitled Kolombio bo Ngana Pailu (The Giant and the Orphan) (Lasipi, 1999) and Topeande (The Man-eating Giant) (Kareba, 1999). By examining the use of affect, judgement, and appreciation, this research figures out that negative attitudes dominantly characterize both human and giant characters. Out of 89 linguistic items in the data, human characters are characterized by 43 negative attitudes, while giant characters are characterized by 20 negative attitudes. Interestingly, by the positive attitudes, the human characters are predominantly depicted as superior in their cognitive abilities and skills. It provides the depiction of the way the two folktales present the human and giant characters. Meanwhile, giants are more dominant than humans in terms of their physical power and strength. This research also suggests that linguistic analysis can support storytelling activities by providing in-depth, objective discussions on the tales.